Sistem Informasi Penyewaan Alat Berat Berbasis Web Pada PT. Akta Trisad - Aini, Syarifah; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2022)
AKTA TRISAD is one of the businesses engaged in the rental of heavy equipment. The problems that occurred at PT. AKTA TRISAD, namely the frequent occurrence of repeated rentals, difficulty in searching for data and difficulties in disseminating information regarding heavy equipment rental. The purpose of this research is to design a web-based heavy equipment rental system at PT. AKTA TRISAD. The method used in system design is the prototyping method. While the system modeling tools used by the author are Use Case Diagrams, Activity Diagrams, Class Diagrams. This rental information system prototype is expected to facilitate PT. AKTA TRISAD in carrying out the process of renting heavy equipment and facilitating the dissemination of required information. So as to be able to produce the required information quickly, precisely and accurately.